Digital Transformation in Financial Risk Management: Opportunities, Challenges, and Future Trends - Deni Sunaryo; Hamdan Hamdan; Dita Ayu Pramesylia; Wilda Oktariani; Ema Imelda (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
The integration of digital technologies such as artificial intelligence (AI), blockchain, and big data analytics into financial risk management has substantially altered operational dynamics within various industries. This paper explores the dual-edged impact of these technologies, emphasizing both the opportunities they create and the challenges they present. Opportunities discussed include enhanced decision-making through advanced data processing, increased transactional transparency and security via blockchain, and improved operational efficiencies through automation. Conversely, the challenges encompass heightened cybersecurity risks, evolving regulatory compliance demands, costly technological integrations, and the emerging skill gaps in managing these digital tools. The paper further investigates the implications of these transformations for different sectors including banking, SMEs, and the construction industry. Each sector faces unique challenges and benefits from the adoption of these technologies. Future trends suggest a continued evolution influenced by technological innovation and regulatory changes. The paper underscores the necessity for ongoing research and adaptive strategies to fully leverage digital advancements in managing financial risks. By understanding these dynamics, financial institutions can better navigate the complexities of the digital age, ensuring robust risk management and a competitive edge in the global market.